High-grade MRI bone oedema is common within the surgical field in rheumatoid arthritis patients undergoing joint replacement and is associated with osteitis in subchondral bone. Issue 12 (9th May 2007) - McQueen, F M; Gao, A; Østergaard, M; King, A; Shalley, G; Robinson, E; Doyle, A; Clark, B; Dalbeth, N
Abstract : Objectives: MRI bone oedema has been observed in early and advanced RA and may represent a cellular infiltrate (osteitis) in subchondral bone. We studied MRI scans from RA patients undergoing surgery, seeking to identify regions of bone oedema and examine its histopathological equivalent in resected bone. Methods: Preoperative contrast-enhanced MRI scans were obtained in 11 RA patients scheduled for orthopaedic surgery to the hands/wrists or feet. In 9, MRI scans were scored by 2 readers for bone oedema (RAMRIS system). Its distribution with respect to surgical site was investigated. In 4 patients, 7 bone samples were examined for a cellular infiltrate, and this was compared with MRI bone oedema, scored for spatial extent and intensity. Results: Inter-reader intraclass correlation coefficients for bone oedema were 0.51 (all sites) and 0.98 (bone samples for histology). Bone oedema was observed at 60% of surgical sites vs 38% of non-surgical sites. High-grade bone oedema (score ⩾50% maximum) was strongly associated with the surgical field (OR 9.3 (3.5 to 24.2), p<0.0001). Bone oedema scores correlated with pain (r = 0.67, p = 0.048) and CRP (r = 0.86, p = 0.01). In 4 of the 7 bone samples, there was concordance between bone oedema and subchondral osteitis. In 3, there was no MRI bone oedema, and osteitis was "slight". Conclusion: High-grade MRI bone oedema was common within the field of intended surgery and associated with pain. There was concordance between the presence and severity of MRI bone oedema and osteitis on histology, with an MRI threshold effect due to differences in image resolution.